Determination of excitation capacitance of a three-phase self-excited induction generator - Maswood, Ali I. (2013)
This paper proposes a simple method of determining the size of excitation capacitance required to buildup a predetermined no load voltage for off-grid operation of a three-phase self-excited induction generator. The method is based on the combination of the principle of L-C resonance and non-linear magnetization characteristic of the generator. For given values of voltage and speed, the magnetizing reactance of the generator is first determined from the solution of a polynomial. The size of the excitation capacitance is then obtained from the principle of L-C resonance. The effectiveness of the proposed method is checked through a more sophisticated generator model where the electrical characteristics are represented by four first-order differential equations. The voltage build-up process in time domain is also investigated through the above model. The results obtained by the proposed method are also verified through an experimental setup consisting of a 1.5-kW induction machine and are found to be in very good agreement.